Demographic, Clinical, and Imaging Characteristics of Canine Patients with Liver Enzyme Alterations Treated at a Veterinary Center in Lima, Peru (2019-2023) - Laguna, Mirella (2024)
This study aimed to describe the demographic, clinical, and imaging characteristics of canine patients with liver enzyme alterations treated at a veterinary center in Lima, Peru, during the 2019-2023 period. The study design was observational, descriptive, and cross-section. The sampling was non-probabilistic and census-based. A total of 116 medical records were reviewed, and the variables considered included demographic characteristics (sex, breed, age), clinical (signs), blood biochemistry (alanine aminotransferase [ALT], aspartate aminotransferase [AST], and alkaline phosphatase [ALP]), and ultrasonographic findings. The database was organized using Microsoft Excel (version 16), processed, and analyzed with descriptive statistics using STATA software (version 18). The most frequent demographic characteristics were male sex (56.03%; n = 65), mixed breed (52.59%; n = 61), and adult age (44.83%; n = 52). The predominant clinical signs in males, females, mixed, and pure breeds were vomiting, diarrhea, anorexia, abdominal pain, lethargy, and fever. Biochemical values were elevated for all three enzymes evaluated, with ranges of AST 53-710 U/L, ALT 68-710 U/L, and ALP 105-1596 U/L. Finally, the most notable ultrasonographic findings were regular borders, increased size, homogeneous parenchyma, and increased echogenicity. It is concluded that 10.34% (n = 12) of patients were in the acute phase, presenting increased vessel caliber, decreased echogenicity, enlarged liver size, and elevated enzyme levels (ALT, AST, and ALP). Additionally, 9.48% (n = 11) were in the chronic phase, characterized by irregular borders, increased echogenicity, normal/preserved liver size, and heterogeneous parenchyma.